Incorporating problem-based learning in transport engineering pedagogy to meet industry needs - Mhlanga, Zenzile Philomena (Stellenbosch : Stellenbosch University, 2025)
Mhlanga, Z. P. 2025. Incorporating Problem-Based Learning in Transport Engineering pedagogy to meet industry needs. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/8d754c9f-7fd3-4614-b963-78fc6fc574a8